Original paperTHE EFFECT OF ENDURANCE, RESISTANCE AND CONCURRENT TRAINING ON THE HEART STRUCTURE OF FEMALE STUDENTS - Hosseini, M.; Piri, M.; Agha-Alinejad, H.; Haj-Sadeghi, Sh. (Biology of Sport, 2012)
The aim of this study was to compare the effect of endurance, resistance and concurrent training on the heart structure. Thirty-nine untrained female students (mean age 24±2.58 yrs) were randomly divided into four groups: Control (C; n=9), Endurance (E; n=10), Strength (S; n=10) and Concurrent (SE; n=10).E group training consisted of running at 65% of maximum heart rate (MHR) for 16 min per training unit during the first week, reaching 80% of MHR for 30 min during the 8th week. S group training consisted of performing four leg presses, bench presses, pull down curls, and leg curls. During the first week, the training was performed at 50% of one repetition maximum (1RM) in 2 sets with 10 repetitions. The intensity of training increased to 80% 1RM in 3 sets and 6 repetitions during the 8th week. The SE training included the sum of the training performed by the E and S training groups. Left ventricular end diastolic and systolic diameters, post-wall thickness, left ventricular mass and mass index and septum wall thickness were measured by m-mode and 2-D echocardiography as the structural parameters. The end diastolic diameter in E and SE groups, the ventricular end systolic diameter, left ventricular mass and mass index of the SE group after the training increased (P≤0.05). In comparing the groups, only the increase of the end diastolic diameter in the SE group was significant (P≤0.05). The 8 weeks of concurrent training compared with endurance or resistance training alone resulted in a significant increase in left ventricular end diastolic diameter. However, no significant differences were found for any other measured variables.